The Function of Gas Vesicles in Halophilic Archaea and Bacteria: Theories and Experimental Evidence - Aharon Oren (Life, 2012)
A few extremely halophilic Archaea (Halobacterium salinarum, Haloquadratum walsbyi, Haloferax mediterranei, Halorubrum vacuolatum, Halogeometricum borinquense, Haloplanus spp.) possess gas vesicles that bestow buoyancy on the cells. Gas vesicles are also produced by the anaerobic endospore-forming halophilic Bacteria Sporohalobacter lortetii and Orenia sivashensis. We have extensive information on the properties of gas vesicles in Hbt. salinarum and Hfx. mediterranei and the regulation of their formation. Different functions were suggested for gas vesicle synthesis: buoying cells towards oxygen-rich surface layers in hypersaline water bodies to prevent oxygen limitation, reaching higher light intensities for the light-driven proton pump bacteriorhodopsin, positioning the cells optimally for light absorption, light shielding, reducing the cytoplasmic volume leading to a higher surface-area-to-volume ratio (for the Archaea) and dispersal of endospores (for the anaerobic spore-forming Bacteria). Except for Hqr. walsbyi which abounds in saltern crystallizer brines, gas-vacuolate halophiles are not among the dominant life forms in hypersaline environments. There only has been little research on gas vesicles in natural communities of halophilic microorganisms, and the few existing studies failed to provide clear evidence for their possible function. This paper summarizes the current status of the different theories why gas vesicles may provide a selective advantage to some halophilic microorganisms.